Use of a Fogarty embolectomy catheter as a bronchial blocker through a single-lumen endotracheal tube in a patient with tracheal narrowing - Kumar, Harish; Ankita (International Journal of Research in Medical Sciences, 2025)
Techniques for single lung ventilation include a double-lumen tube, Univent or a bronchial blocker. However, the larger outer diameter of double-lumen or Univent tubes may pose problem in its passage through an area of subglottic stenosis or tracheal narrowing. Here, we report our experience in a case of tracheal narrowing due to extraluminal compression by mediastinal mass in which a Fogarty embolectomy catheter was used as a bronchial blocker through a single lumen endotracheal tube (ETT). Fogarty embolectomy catheter may be a suitable option for one lung ventilation (OLV) in tracheal narrowing, where there is limitation to use double lumen tube or Univent tube.